Relative prevalence and distribution of knee, hand and foot symptomatic osteoarthritis subtypes in an English population. (29th January 2020) - Peat, George; Rathod‐Mistry, Trishna; Paskins, Zoe; Marshall, Michelle; Thomas, Martin J.; Menz, Hylton B.; Nicholls, Elaine; Myers, Helen; Duncan, Rachel; van der Windt, Danielle A.; Roddy, Ed; Dziedzic, Krysia S.
Abstract: In this brief report, we used data from a series of three related cohorts on pain and osteoarthritis (OA) of the knee, hand and foot, which were conducted in North Staffordshire, England. We used a common approach for sampling, data collection and coding, to estimate the relative prevalence of 10 different symptomatic radiographic OA subtypes in the knee, hand and foot and to compare their association with age, sex, socioeconomic position and body mass index. Overall, symptomatic hand OA was more common than knee or foot OA (22.4% vs 17.4% vs 16.5%), due mainly to the high prevalence of nodal interphalangeal joint OA among women. The first carpometacarpal joint OA was the most frequent subtype, with patellofemoral, tibiofemoral, (nodal) interphalangeal and midfoot OA also common. Of the risk factors examined, the greatest differences between subtypes appeared to be their associations with sex and obesity: sex differences were noticeably greater for all forms of hand OA except non‐nodal interphalangeal joint OA, while obesity appeared most strongly associated with forms of knee OA. The prevalence of all subtypes was higher among older ages, and among those with lower educational attainment.